An integrated African pastoral care approach to unaccompanied refugee minors based on Verryn"s Child interventions - Chisale, Sinenhlanhla S. (HTS teologiese studies, 2019)
The African proverb ‘it takes a village to raise a child’ has been compromised and exposed by the migration of Unaccompanied Refugee Minors (URMs) from Zimbabwe to South Africa. Written from African women’s perspective, this article explores the response and approach of Bishop Paul Verryn to URMs. The article theologises Verryn’s response to URMs in conversation with African values, themes or sayings that relate to childcare, mainly from a Zimbabwean Ndebele context, and through the lens of the African saying ‘It takes a village to raise a child’. In the findings, three crucial socio-ecclesial themes emerge from Verryn’s response which I refer to as the three Cs, namely, collaboration, consultation and contextuality. These are discussed through the lens of African women’s theology in relation to African values of childcare and its implications for pastoral care in a context of displaced children, and accompanied or unaccompanied minors (child migrants).